2015
DOI: 10.3389/fnhum.2015.00126
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and motion metaphors have different scalp distributions: an ERP study

Abstract: While many links have been established between sensory-motor words used literally (kick the ball) and sensory-motor regions of the brain, it is less clear whether metaphorically used words (kick the habit) also show such signs of “embodiment.” Additionally, not much is known about the timing or nature of the connection between language and sensory-motor neural processing. We used stimuli divided into three figurativeness conditions—literal, metaphor, and anomalous—and two modality conditions—auditory (Her limo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Both the CSC theory and the GSH therefore suggest that literal language is primarily processed in the LH, whereas the RH has privileged access to the figurative aspects of novel metaphorical expressions. The hypothesis of a relationship between lower and higher levels of RH language is also supported by results obtained by Schmidt-Snoek et al (2015), who recently showed, in an event-related potential study, that words used metaphorically show signs of "embodiment", confirming the neural links between metaphors and sensory-motor aspects of experience. No conflict exists, therefore, between the older, lower-level models of RH language, based on selective, coarse-grained, semantic lexical knowledge, and the more recent models which maintain that the RH plays an important role in the use of higher-level language functions, such as metaphors, to convey complex, abstract concepts.…”
Section: Right Hemisphere Languagesupporting
confidence: 62%
“…Both the CSC theory and the GSH therefore suggest that literal language is primarily processed in the LH, whereas the RH has privileged access to the figurative aspects of novel metaphorical expressions. The hypothesis of a relationship between lower and higher levels of RH language is also supported by results obtained by Schmidt-Snoek et al (2015), who recently showed, in an event-related potential study, that words used metaphorically show signs of "embodiment", confirming the neural links between metaphors and sensory-motor aspects of experience. No conflict exists, therefore, between the older, lower-level models of RH language, based on selective, coarse-grained, semantic lexical knowledge, and the more recent models which maintain that the RH plays an important role in the use of higher-level language functions, such as metaphors, to convey complex, abstract concepts.…”
Section: Right Hemisphere Languagesupporting
confidence: 62%
“…The ERP studies of metaphors have frequently reported a biphasic pattern, with a centro-parietal negativity (N400) and a later parietal positivity (P600) (e.g., Coulson and Van Petten, 2002; De Grauwe et al, 2010; Weiland et al, 2014; Schmidt-Snoek et al, 2015; Bambini et al, 2016). Studies finding a later effect (P600) tend to favor the indirect access model, while those finding an N400 component argue for a direct access view.…”
Section: Introductionmentioning
confidence: 99%
“…When the event-related potential (ERP) electrophysiological technique started to be used to investigate how metaphor comprehension unfolds over time, the issue of the processing steps was revived in terms of ERP components (Bambini and Resta, 2012 ; Rataj, 2014 ). Two components have been commonly reported for metaphors, namely a centro-parietal negativity (N400) and a later parietal positivity (P600/LPC) (Pynte et al, 1996 ; Coulson and Van Petten, 2002 ; De Grauwe et al, 2010 ; Schmidt-Snoek et al, 2015 ). The functional roles of these components in language processing are diverse.…”
Section: Introductionmentioning
confidence: 99%